Promoting Speaking Skill through Engage-Study-Active for Indonesian Vocational Students - Yuniasih, Dewati (Budapest International Research and Critics University, 2022)
The purpose of this study is to illustrate the use of the engage study active, adapted from Harmer (2007) and the conventional teacher-centered method at vocational school in Lampung, Indonesia. Researchers used quasi-experiments using an experiment and a control class with a sample of 73 students. The results of the sample paired t test statistics show that there is a sharp difference between the uses of the two teaching methods. Teaching with English study active can enrich students' vocabulary, increase student motivation, and make the learning process more active.